2003
DOI: 10.1002/cncr.11912
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary nonpolyposis colorectal carcinoma (HNPCC) and HNPCC‐like families: Problems in diagnosis, surveillance, and management

Abstract: BACKGROUND To the authors' knowledge, hereditary nonpolyposis colorectal carcinoma (HNPCC) is the most commonly occurring hereditary disorder that predisposes to colorectal carcinoma (CRC), accounting for approximately 2–7% of all CRC cases diagnosed in the U.S each year. Its diagnosis is wholly dependent on a meticulously obtained family history of cancer of all anatomic sites, with particular attention to the pattern of cancer distribution within the family. METHODS The objective of the current study was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
53
0
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 38 publications
1
53
0
3
Order By: Relevance
“…Approximately 10 -20% of sporadic CRC tumours have been reported to be MSI-H (Imai and Yamamoto, 2008), and the corresponding proportion in our study was 17%. The prevalence of CRCs associated with LS has been 3 -5% in most studies (de la Chapelle, 2004;Lynch et al, 2004;Vasen et al, 2007), and on the basis of molecular tumour tests, we estimated a prevalence of 3.6%. Most studies of unselected CRC patients have analysed MLH1 and MSH2 genes, as these are most commonly mutated in LS (de la Chapelle, 2004;Domingo et al, 2004;Julie et al, 2008).…”
Section: Clinical Guidelines In Identifying Ls G Tranø Et Almentioning
confidence: 94%
See 2 more Smart Citations
“…Approximately 10 -20% of sporadic CRC tumours have been reported to be MSI-H (Imai and Yamamoto, 2008), and the corresponding proportion in our study was 17%. The prevalence of CRCs associated with LS has been 3 -5% in most studies (de la Chapelle, 2004;Lynch et al, 2004;Vasen et al, 2007), and on the basis of molecular tumour tests, we estimated a prevalence of 3.6%. Most studies of unselected CRC patients have analysed MLH1 and MSH2 genes, as these are most commonly mutated in LS (de la Chapelle, 2004;Domingo et al, 2004;Julie et al, 2008).…”
Section: Clinical Guidelines In Identifying Ls G Tranø Et Almentioning
confidence: 94%
“…It has been suggested that up to 20 -25% of CRC cases are familial, including heredity caused by identified genetic factors and familial clustering of CRC in which the hereditary patterns are complex or unknown (de la Chapelle, 2004). Lynch syndrome (LS) constitutes 3 -5% of all CRCs (Lynch et al, 2004). In individuals with this autosomal dominant predisposition, CRC tends to develop B20 years earlier than sporadic CRC, and the lifetime risk for CRC is 50 -80% (de la Chapelle, 2004;Strate and Syngal, 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Females at 25-35 years of age should undergo annual transvaginal ultrasonography, endometrial aspirations, and have CA-125 levels checked. Oesophagogasrtoduodenoscopy can be utilised in patients to screen for gastric cancer and ultrasound and urine cytology can be utilised to screen for urinary tract malignancy [11]. Surgical management for patients with HNPCC, when elected, includes either a prophylactic total abdominal colectomy with IRA or a segmental colectomy with yearly colonoscopy [12].…”
Section: Hereditary Colorectal Cancer Syndromesmentioning
confidence: 99%
“…MLH1 promoter region methylation, leading to silencing of this gene, is an alternative mechanism to mutation underlying MSI-H in sporadic CRC (Toyota et al, 1999). Genetic testing for hereditary predisposition is therefore critical for effective management of suspected HNPCC kindreds (de la Chapelle, 2004;Lynch et al, 2004;Hampel et al, 2005).…”
mentioning
confidence: 99%